2018
DOI: 10.2139/ssrn.3307535
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating Task Acquisition from Expression During Learning Reveals Latent Knowledge

Abstract: Performance on cognitive tasks during learning is used to measure knowledge, yet it remains controversial since such testing is susceptible to contextual factors. To what extent does performance during learning depend on the testing context, rather than underlying knowledge? We trained mice, rats and ferrets on a range of tasks to examine how testing context impacts the acquisition of knowledge versus its expression. We interleaved reinforced trials with probe trials in which we omitted reinforcement. Across t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…Thus, goal-oriented behavior can sometimes operate in two phases: first, a latent learning phase in which an animal explores and acquires an internal model of the structure of its environment, and second, a phase in which the animal modifies its behavior in that environment through its good or bad experiences in specific situations and/or places [10]. Many studies of learned behavior and its neural correlates, particularly those involving mammals, focus on the second phase, using trained animals that have already learned the basic structure of tasks and environments; in doing so, they study task performance more than task acquisition (but see, for example, [11][12][13][14][15]). By contrast, in many natural settings, animals must develop internal representations of their spatial relationship to their surroundings at the same time that they discover the environment's rules through reinforcement of specific actions or contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, goal-oriented behavior can sometimes operate in two phases: first, a latent learning phase in which an animal explores and acquires an internal model of the structure of its environment, and second, a phase in which the animal modifies its behavior in that environment through its good or bad experiences in specific situations and/or places [10]. Many studies of learned behavior and its neural correlates, particularly those involving mammals, focus on the second phase, using trained animals that have already learned the basic structure of tasks and environments; in doing so, they study task performance more than task acquisition (but see, for example, [11][12][13][14][15]). By contrast, in many natural settings, animals must develop internal representations of their spatial relationship to their surroundings at the same time that they discover the environment's rules through reinforcement of specific actions or contexts.…”
Section: Introductionmentioning
confidence: 99%
“…This increase in d ’ was driven by a more pronounced reduction of false alarm rate ( FAR ) than hit rate ( HR; ΔFAR - ΔHR = −0.07 ± 0.08, t 59 = −6.42, p <.001, Cohen’s d = −0.83). However, both measures decreased significantly in probe compared to pre-probe trials ( ΔHR = −0.08 ± 0.06, t 59 = −9.67, p <.001, Cohen’s d = −1.25; ΔFAR = −0.15 ± 0.08, t 59 = − 15.12, p <.001, Cohen’s d = −1.95, Fig 2C/D), while in (12) only a decrease in false alarm rate during probe trials was reported. Once reinforcement was reinstated, d ’ significantly decreased again ( Δd ’ = 0.15 ± 0.47, t 59 = 2.40, p =.020, Cohen’s d = 0.31, see Fig 7 in S1 Appendix).…”
Section: Resultsmentioning
confidence: 94%
“…Based on recent findings in rodents (12), we hypothesized that the performance of humans in an instrumental learning task increases during non-reinforced compared to reinforced periods. Therefore, we designed a visual go/no-go reinforcement learning task (Fig 1A ) consisting of reinforced trials which were interleaved with five probe blocks of non-reinforced trials.…”
Section: Taskmentioning
confidence: 99%
See 2 more Smart Citations